The relationship between feeding patterns and nutritional status of toddlers - Selvyra Eka Masturina; Koekoeh Hardjito; Dwi Estuning Rahayu (Institute of Computer Science (IOCS), 2023)
Malnutrition or undernutrition is a condition of someone who has nutrients below the average number. Lack of nutrition is caused because a person lacks the intake of carbohydrates, proteins, fats, and vitamins that are needed by the body. A good nutritional status of children can meet growth and development, and good child health. This study was conducted to determine the relationship between feeding patterns and the nutritional status of toddlers. The method used in this study is a literature review of the results of the 2016-2022 research that has been published in electronic media such as Google Scholar, Pubmed, Science Direct, and Pro-Quest. The number of full-text articles searched that meet the inclusion criteria is 10. The results of this study found that feeding patterns are closely related to the nutritional status of toddlers. The conclusion of this study is the relationship between feeding patterns and the nutritional status of toddlers. It is expected for parents or caregivers to better understand and apply nutritious food for toddlers to grow and develop optimally.